2017
DOI: 10.1007/s00063-017-0378-6
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressors for acute myocardial infarction complicated by cardiogenic shock

Abstract: Several international evidence-based guidelines reveal the lack of evidence on the treatment of patients with acute myocardial infarction (AMI) complicated by cardiogenic shock (CS) for all recommended therapies. We included 6 studies with 842 eligible patients and one ongoing study. Three different adrenergic agents (norepinephrine, dopamine, epinephrine), vasopressin and the NOS inhibitor tilarginine were compared in 4 different combinations. On the small basis of all available evidence we can state that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…comparing the effects of vasopressor agents in patients with CS (5)(6)(7). In a randomized study comparing dopamine and norepinephrine (8), a subgroup analysis of 280 patients with CS found that dopamine was associated with increased 28-day mortality compared with norepinephrine, leading to a progressive decrease in dopamine use in this indication (9).…”
mentioning
confidence: 99%
“…comparing the effects of vasopressor agents in patients with CS (5)(6)(7). In a randomized study comparing dopamine and norepinephrine (8), a subgroup analysis of 280 patients with CS found that dopamine was associated with increased 28-day mortality compared with norepinephrine, leading to a progressive decrease in dopamine use in this indication (9).…”
mentioning
confidence: 99%